2016
DOI: 10.18632/oncotarget.10401
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variations in the Wnt signaling pathway genes with myocardial infarction susceptibility in Chinese Han population

Abstract: Numerous studies have implicated the Wnt pathway in the development and progression of myocardial infarction (MI); however, there are very few investigations addressing the effects of polymorphisms in the Wnt pathway genes on MI susceptibility. We investigated the possible correlation between genetic variations in Wnt pathway genes and MI risk. Three polymorphisms (rs7832767 C > T in SFRP1 gene, rs2293303 C > T in CTNNB1 gene, rs16893344 C > T in WISP1 gene) were finally selected and genotyped in 465 MI patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Another study also concluded that the migratory machinery of cells was associated with LRG1, because their activities were altered as observed in their performance within the non-canonical TGF-β signaling pathway 12 . Compelling evidence has identified the involvement of the Wnt signaling pathway in MI,13, 14 and that it was activated in MI as a potential therapeutic target 14, 15, 16. The Wnt signaling pathway is known to serve as a stem cell pathway, which is critical for embryogenesis and the transcription of downstream members of the pathway 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study also concluded that the migratory machinery of cells was associated with LRG1, because their activities were altered as observed in their performance within the non-canonical TGF-β signaling pathway 12 . Compelling evidence has identified the involvement of the Wnt signaling pathway in MI,13, 14 and that it was activated in MI as a potential therapeutic target 14, 15, 16. The Wnt signaling pathway is known to serve as a stem cell pathway, which is critical for embryogenesis and the transcription of downstream members of the pathway 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, Chen et al [ 22 ] indicated that lung cancer patients carrying the T allele of the WISP1 rs16893344 polymorphism may have an increased risk of lung cancer. Tao et al also showed that WISP1 rs16893344 C > T polymorphisms significantly increased myocardial infarction risk [ 39 ]. These results demonstrate that the various WISP1 SNPs may be expressed in different cancers and diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained when bone marrow cells of sFRP1 overexpressing mice were transplanted in wild-type recipients, which subsequently were subjected to MI ( Barandon et al, 2011 ). A genetic variant of sFRP1 was reported to be associated with an increased risk of MI in a Chinese Han population ( Tao et al, 2016 ). An anti-inflammatory and antiapoptotic role for sFRP5 has also been described in a mouse model of ischemia/reperfusion damage ( Nakamura et al, 2016 ), supporting a beneficial effect of sFRPs on infarct healing.…”
Section: Wnt Signaling In Cardiac Diseasementioning
confidence: 99%